Governing finance in Europe: a centralisation of rule-making? (2020)
The governance of finance in Europe is embedded in international regulatory agreements. Especially since the financial crisis of 2008, international agreements have sought to introduce rules to ensure that micro-risks (failures to maintain financial contracts) and macro-risks (contagion, leading to system-stability risks) are reduced. The implementation of international regulations in European regulations and, as a result, in national regulations, has had important repercussions on the regulatory structure of the European Union. Did these changes lead to a centralisation reflected in a shift of formal rule-making and the supervision of its implementation from the national to the supranational level? If so, why did this happen and through which processes? Who wins and who loses from this shift? Finally, what are the implications for political accountability in rule-making?